Introducing theme-based listening materials into English writing: Focusing on learner affectivity - Uenishi, Koji (Archives of Business Research, 2021)
Recently, in the global society the focus in foreign language education has tended to be on productive skills from elementary school through university. It is natural that when we try to communicate with other people in English, in addition to receptive skills (input), productive skills (output) are also important to convey our feelings and thoughts to others. In order to make ourselves understood through language, the language–related input is vital; then we need to acquire sufficient productive skills through it. That is to say, without input, output cannot be possible. This research attempts to enhance the quality and quantity of input by using listening materials in a writing class as one of the useful activities for input. This leads to writing activities being carried out as output. In this case, the class contents which will be useful for the learners in their future careers are adopted. From this perspective, the relevance between listening and writing activities is explored.